A case of butane hash oil (marijuana wax)–induced psychosis. Issue 3 (2nd July 2016) - Keller, Corey J.; Chen, Evan C.; Brodsky, Kimberly; Yoon, Jong H.
ABSTRACT: Background : Marijuana is one of the most widely used controlled substances in the United States. Despite extensive research on smoked marijuana, little is known regarding the potential psychotropic effects of marijuana "wax, " a high-potency form of marijuana that is gaining in popularity. Case : The authors present a case of "Mr. B, " a 34-year-old veteran who presented with profound psychosis in the setting of recent initiation of heavy, daily marijuana wax use. He exhibited incoherent speech and odd behaviors and appeared to be in a dream-like state with perseverating thoughts about his combat experience. His condition persisted despite treatment with risperidone 4 mg twice a day (BID), but improved dramatically on day 8 of hospitalization with the return of baseline mental function. Following discharge, Mr. B discontinued all marijuana use and did not exhibit the return of any psychotic symptoms. Discussion : This study highlights the need for future research regarding the potential medical and psychiatric effects of new, high-potency forms of marijuana. Could cannabis have a dose-dependent impact on psychosis? What other potential psychiatric effects could emerge heretofore unseen in lower potency formulations? Given the recent legalization of marijuana, these questions merit timely exploration.